Dissemination and characteristics of carbapenem-resistant Klebsiella pneumoniae in nine district hospitals in southwestern China - Wang, Yonghong; Ouyang, Yan; Xu, Xiuyu; Sun, Shan; Tian, Xiaolang; Liu, Hang; Xia, Yun (Frontiers in Microbiology, 2023)
Importance: current studies on the epidemiology and antimicrobialresistant characteristics of CRKP and/or HV-CRKP mainly concentrated on large tertiary teaching hospitals and ignored the district-level hospitals.In our study, we found that CRKP strains exhibited a high level of antibiotic resistance, a high proportion of harboring carbapenemases, and hypervirulence phenotype in district hospitals in Southwest, China. These results will further provide support for the prevention and control of nosocomial infection by CRKP in secondary medical institutions.